(untitled) (Architecture Image Studies, 2023)
Commercial structures are beginning to appear in many regions of Bali, resulting in increased congestion and visual saturation. As a result, many designers have begun to incorporate aesthetic features into their designs in order to boost the building’s appeal and pique people’s interest in visiting it.The purpose of this study was to learn about Balinese people’s perceptions of aesthetics, or the beauty of form, so that the fabrication of aesthetic elements for commercial building facades can match Balinese residents’ aesthetic requirements.To help the public react to research questions about designs, materials, and colors in the aesthetic elements of commercial building facades, researchers used qualitative approaches such as observations and surveys. Following that, the investigation was conducted.